Analisis Kesulitan yang Dialami Guru dalam Pembuatan RPP di SDN 060843 Medan - Marintan Evelyn Marbun; Laurensia Masri Perangin Angin; Nazuani Husna; Rahmi Khairani Ritonga; Suhail Anshari (Jurnal Pendidikan Indonesia, 2022)
The 2013 curriculum is the applicable curriculum in the Indonesian Education System. Four aspects of the 2013 Curriculum assessment, namely aspects of knowledge, aspects of skills, aspects of attitudes, and behavior. There are materials that are streamlined and added to the 2013 curriculum. The streamlined material can be seen in the Indonesian language material, Social Studies, PPKn, etc. While the material added is Mathematics material. This study aims to determine the difficulties experienced by teachers in making lesson plans. The method of data collection in this study used an interview instrument. The survey research method with a quantitative approach (Quantitative Research) is the research method chosen in this study to answer research questions. The variable that became the main reference for the researcher was to conduct an interview with one of the relevant school teachers to answer questions about the difficulties of teachers in making lesson plans (RPP). The research location is at SDN 060843 Medan. The results of the study revealed that it was difficult for teachers to describe KD into indicators, difficult to arrange learning steps in lesson plans, difficult to adapt methods, difficult to make their own media, and difficulties in adapting teaching materials to students. The teacher's lack of understanding regarding matters relating to the implementation of scientific approach learning makes some activities in the scientific approach not run optimally. Since it was implemented in July 2014, many problems have been faced by teachers in developing lesson plans according to the 2013 curriculum. Another difficulty is the use of operational words Bloom's Taxonomy in the formulation of indicators in the preparation of lesson plans. Along with the governance that must be met by teachers, both assessment and management of learning based on the 2013 curriculum, so it is important to examine what difficulties are experienced by subject teachers in preparing lesson plans in accordance with the 2013 curriculum